Homogeneity Assessment of Asphalt Concrete Base in Terms of a Three-Dimensional Air-Launched Ground Penetrating Radar - Xiaomeng Zhang (MDPI AG, 2021)
Obtaining the required homogeneity, including uniform thickness and density, is very crucial for controlling the quality of flexible asphalt layers. Although non-destructive testing (NDT) methods are time-saving and less labor-intensive, they only provide indirect measurement data under testing area conditions and strongly depend on the explanations by prediction models. In this study, in terms of the three-dimensional air-launched Ground Penetrating Radar (GPR) technique, the dielectric constant of asphalt concrete base with dry conditions in pavements was detected and calculated by different methods (the Coring Method, Reflection Amplitudes Method and Common Mid-Point Method). According to the calculated dielectric constant, the thickness and density of asphalt concrete base were further calculated and assessed. Comparing with the Coring Method, the Common Mid-Point Method was recommended to calculate dielectric constants in order to obtain reliable thickness of asphalt pavement base. Among the Birefringence, Boettcher, Linearity indicator, and Rayleigh models, the Rayleigh model was suggested to predict the density, and the predicted density exhibited a good correlation coefficient with the measured one. Furthermore, by choosing these proper calculation methods, an assessment was successfully conducted to evaluate homogeneity of a constructed field pavement in practice.